The Influence of Digital Literacy in Social Media Use on High School Students’ Intrinsic Motivation in EFL Learning - Assyfa Aprilia Sari; Sri Kusuma Ningsih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Digital literacy in the context of social media use has become an important aspect of English language learning for students. However, despite the increasing integration of digital technologies in education, there remains a gap in understanding how students’ use of social media as part of their digital literacy relates to their intrinsic motivation for learning English. This study aims to examine how digital literacy in social media use influences high school students' intrinsic motivation in EFL learning. It focuses on two dimensions of intrinsic motivation: (1) effort and commitment in learning English and (2) imagination of the future with English. A quantitative method using an adapted questionnaire was employed, involving 220 high school students aged 14–21 in the JABODETABEK area. Regression analysis revealed that digital literacy in social media use significantly affects two dimensions of high school students’ intrinsic motivation: effort and commitment in learning English (R² = 0.221, F = 63.24, p < 0.001) and imagination of the future with English (R² = 0.209, F = 58.84, p < 0.001), both indicating medium effect sizes. Furthermore, multivariate analysis of variance (MANOVA) confirmed a significant simultaneous effect on both motivational constructs (F = 45.2, p < 0.001). These findings suggest that digital literacy in social media use can be an effective strategy to enhance students’ intrinsic motivation in EFL learning. Therefore, this study recommends that EFL teachers thoughtfully integrate selected social media platforms into learning activities to support both digital literacy and motivation.